Histopathological Effect of Several Stages of Chronic Kidney Disease - Alkufaishi, Zainab Hayder Jaber (American Journal of Biomedicine and Pharmacy, 2024)
This investigation was done to study the histopathology feature of several stages of chronic kidney disease. In this cross-sectional research, individuals who undergone radical nephrectomy are included. For each patient, we gathered clinical information both before and after surgery as well as a sample of kidney tissue from the cortex and medulla that was taken at least three centimeters away from the mass but was not affected by the tumor. samples were collected for histological analysis. Following surgery, a kidney tissue sample was taken that measured about 2 * 1.5 cm included both the medulla and cortex (at minimum 3 cm from the tumor). In accordance with accepted practices, all samples were embedded in paraffin and fixed in buffered formalin. Hematoxylin and eosin were used to stain kidney slices that were four microns thick. The present study showed that score 1 was significantly higher than other scores, also stage 2 showed significantly higher than another stages. In histological examination, glomerulosclerosis, extensive tubular atrophy, and interstitial fibrosis appeared among the different stages. Inconclusion, CKD with stage 2 showed significantly higher than another stages.